Aberrant resting-state regional activity in patients with postpartum depression - Li, Bo; Zhang, Shufen; Li, Shuyan; Liu, Kai; Hou, Xiaoming (Frontiers in Human Neuroscience, 2023)
Postpartum depression (PPD) is a common disease, but little is known about its underlying neuropathology. The aim of this study is to investigate the alterations of individual local connectivity by regional homogeneity (ReHo) in patients with PPD during resting state and their potential correlations with clinical severity. Twenty-eight patients with PPD and twenty-nine healthy postpartum women were recruited and received resting-state functional magnetic resonance imaging (fMRI) scans in the fourth week after delivery. The ReHo value was computed as Kendall’s coefficient of concordance (KCC) in the present study, and intergroup differences in the voxel manner were analysed. Correlations between ReHo values and clinical variables were also analysed. Compared with healthy postpartum women, patients with PPD exhibited significantly higher ReHo in the left precuneus and right hippocampus. ReHo was significantly lower in the left dorsolateral prefrontal cortex (dlPFC) and right insula. Furthermore, ReHo values within the dlPFC negatively correlated with the Edinburgh postpartum depression scale (EPDS) score. The receiver operating characteristic (ROC) curve analysis showed the area under the curve of the above four brain regions are all over 0.7. The function connectivity of the left precuneus to the right hippocampus was stronger in PPD patients than in controls. This study provided evidences of aberrant regional functional activity within brain regions involved in the maternal care network in PPD, and it may contribute to further understanding of the neuropathology underlying PPD.